2014
DOI: 10.1016/j.labeco.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The causal effect of trade on migration: Evidence from countries of the Euro-Mediterranean partnership

Abstract: In the attempt to reduce migration pressure, since 1995, the European Union has been planning to establish a free trade area with developing countries bordering the Mediterranean Sea. The process is still ongoing. Our paper tests whether it is likely to be an effective policy. We estimate a gravitational model of bilateral migrations on bilateral exports from the Mediterranean Third Countries (South) to the European Union (North) over the period 1970-2000, using different specifications. We find, in line with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…In this regard, quantitative methods are the best to find relations between various factors in measuring of migration. Indeed, many quantitative studies found economic factors as the leading determinant in the fostering of international migration [23][24][25][26][27][28][29][30][31][32]. Jennissen [33], Balderas and Greenwood [27], Pânzaru [29] and Campaniello [31], analyzed the reasons of international migration in the European Union and identified that economic factors cause people to move to other countries.…”
Section: Theorizing Determinants Of International Migration: Literatumentioning
confidence: 99%
“…In this regard, quantitative methods are the best to find relations between various factors in measuring of migration. Indeed, many quantitative studies found economic factors as the leading determinant in the fostering of international migration [23][24][25][26][27][28][29][30][31][32]. Jennissen [33], Balderas and Greenwood [27], Pânzaru [29] and Campaniello [31], analyzed the reasons of international migration in the European Union and identified that economic factors cause people to move to other countries.…”
Section: Theorizing Determinants Of International Migration: Literatumentioning
confidence: 99%
“…Accordingly, liberalising trade should decrease incentives to migrate. However, if immigrants do prefer goods produced in their country of origin, migration and trade can easily be complements (Campaniello, ). In addition, migration can also reduce trade costs (see, for instance, Felbermayr and Toubal, ).…”
Section: Introductionmentioning
confidence: 99%
“…A paper that is somewhat related to this literature and which has important links with our research question is Campaniello (2014). This paper looks at the effect of trade on migration using a gravity model and, at the same time, addresses the endogeneity issue of trade flows.…”
Section: The Gravity Model For Interpreting Migration Movementmentioning
confidence: 99%
“…Empirically, the positive correlation is particularly evident. Intuitively these two variables might be positively related because of the role of aggregate bilateral trade relations; as argued by Campaniello (2014) trade per se (imports of cultural and non-cultural are positively correlated Fig.1b) enhances links between countries and migrants may utilize these links to enter the receiving country. To tackle this issue, we adopt an empirical approach that disentangles the effect of cultural products from the more general impact of aggregate trade.…”
Section: Figure 1b: Correlation Between Aggregate Imports and Culturamentioning
confidence: 99%